In vitro selection for NaCl salt tolerance in aromatic rice (Oryza sativa) genotypes - HASAN, M; SARKER, R H (The Indian Journal of Agricultural Sciences, 2026)
Dehusked seeds of eight aromatic rice (Oryza sativa L.) varieties as parents and their F1 and F2 generations were placed on MS media supplemented with NaCl salt at four different levels (0%, 0.2%, 0.4% and 0.6%) to observe the callus induction and plant regeneration responses. For callus induction MS medium was supplemented with 2 mg/L 2,4 D while for plant regeneration MS medium was supplemented with 1 mg/L NAA and BAP. All the genotypes showed significant variation in callus induction and plant regeneration responses. Callus induction and plant regeneration percentage decreased with the increase of salt doses. While checking the response of parents under NaCl stress, the highest callus induction was found in Jirabhog and Badshahbhog (70%). Uknimadhu was best in plant regeneration (37.5%). For F1 generation, Uknimadhu × Chinishakkhor showed the highest callus induction response (70). Uknimadhu × BR 5 was the best performer (27.5%) in plant regeneration response. For F2 generation, Kalijira × Chinishakkhor showed the highest callus induction response (32.5%). For plant regeneration, Uknimadhu ×Kataribhog (10%) was the best. It was concluded that salt tolerant aromatic rice varieties can be obtained employing salt stress in in vitro condition.